2023
DOI: 10.1039/d3tc00079f
|View full text |Cite
|
Sign up to set email alerts
|

Polythiophene-g-poly(methacrylic acid) and perylene diimide appended peptide conjugates with tuneable photoluminescence, OMEIC, and photo-switching properties

Abstract: A water soluble polymer conjugate, composed of poly(thiophene methacrylate) (PTMA) and cationic peptide appended Perylene diimide (PBI-NH3+) was fabricated. The dipolar interaction between PTMA and PBI-NH3+helped to uncoil the polythiophene...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…This can be due to the stronger π−π stacking interactions among the chromophoric π moieties of P 1 inside the hybrid gel matrix than the simply aggregated state of P 1 . 48 In the FEG-TEM image, P 1 has shown the interconnected nanosphere-like structure (Figure S11a). Moreover, we observed the fibril network morphology for the aggregated P 3 in gel state.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This can be due to the stronger π−π stacking interactions among the chromophoric π moieties of P 1 inside the hybrid gel matrix than the simply aggregated state of P 1 . 48 In the FEG-TEM image, P 1 has shown the interconnected nanosphere-like structure (Figure S11a). Moreover, we observed the fibril network morphology for the aggregated P 3 in gel state.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…By applying the bias voltage from +5 to −5 V, the current conductivity of the dry gel has been measured to be 14.1 μA, which suggests the semiconductive nature of the aggregated material. Interestingly, the I – V curve of the dry gel has shown a diode-like nature (Figure a), and this encouraged us to look into whether the dry gel is associated with the mix ion and electron conductivity …”
Section: Resultsmentioning
confidence: 99%
“…The statistical analysis of the dc conductivity has been carried out with 8 different experiments, which also exhibited good reproducible data (Figure S6). Such a good dc current of the NDIP dry gel is probably due to the presence of the conductive nanofiber of the aggregated NDIP in the gel state . In the temperature-dependent resistance analysis, it is observed that the resistance of the dried gel is also gradually decreasing from 0.14 Ω at 35 °C to 0.123 Ω at 85 °C (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations